2017
DOI: 10.1109/tetci.2017.2750761
|View full text |Cite
|
Sign up to set email alerts
|

EEG Analysis for Cognitive Failure Detection in Driving Using Type-2 Fuzzy Classifiers

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The rest of training and testing are similar to the present work. Table-V includes the results of ' E obtained by the 2 proposed T2FS based mapping techniques against traditional type-1 and type-2 fuzzy [51][52][53], [65][66] algorithms, standard deep learning algorithms, including Long Short-Term Memory (LSTM) [67] and Convolutional Neural Network (CNN) [68], and traditional non-fuzzy mapping algorithms including N-th order Polynomial regression [75] E of ~ 1.5%. In Table-V, we also observe that the IT2FS based mapping technique takes the smallest run-time (~34 ms), when compared with the other mapping methods.…”
Section: A Performance Analysis Of the Proposed T2fs Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest of training and testing are similar to the present work. Table-V includes the results of ' E obtained by the 2 proposed T2FS based mapping techniques against traditional type-1 and type-2 fuzzy [51][52][53], [65][66] algorithms, standard deep learning algorithms, including Long Short-Term Memory (LSTM) [67] and Convolutional Neural Network (CNN) [68], and traditional non-fuzzy mapping algorithms including N-th order Polynomial regression [75] E of ~ 1.5%. In Table-V, we also observe that the IT2FS based mapping technique takes the smallest run-time (~34 ms), when compared with the other mapping methods.…”
Section: A Performance Analysis Of the Proposed T2fs Methodsmentioning
confidence: 99%
“…Thus type-2 fuzzy logic is expected to serve well in functional mapping at higher level neural learning. Two distinct varieties of type-2 fuzzy sets are widely being used in the literature [50][51][52][53], [65][66]. They are wellknown as Interval Type-2 Fuzzy Sets (IT2FS) [50] and General Type-2 Fuzzy Sets (GT2FS) [51].…”
Section: Introductionmentioning
confidence: 99%
“…The EEG recordings contain cortical potentials, which occur during various mental processes [2]. These signals comprise of different frequency sub-bands: Delta (4 Hz), Theta (4-7 Hz), Alpha or mu (8-12 Hz), Beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and Gamma (30-100 Hz) bands, to facilitate ease of analysis. Studies presented in [3,4] found out that mu and beta rhythms are more sensitive to correct and incorrect hand grips and respond strongly especially over motor and pre-motor cortex areas of brain.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques based on Computational Intelligence (CI), e.g., artificial neural networks, fuzzy systems, and evolutionary computation, have achieved remarkable results in modelling, learning, searching, and optimisation problems for smart city applications [18], [19], [20]. Deep learning, a relatively "young" learning paradigm in the CI family, has in fact its origin from Artificial Neural Networks (ANNs).…”
Section: Introductionmentioning
confidence: 99%